Do Patients' Psychosocial Characteristics Impact Antibiotic Prescription Rates? - Säde Stenlund; Louise C. Mâsse; David Stenlund; Lauri Sillanmäki; Kirstin C. Appelt; Heli Koivumaa-Honkanen; Päivi Rautava; Sakari Suominen; David M. Patrick (MDPI AG, 2023)
Previous research suggests that the characteristics of both patients and physicians can contribute to the overuse of antibiotics. Until now, patients' psychosocial characteristics have not been widely explored as a potential contributor to the overuse of antibiotics. In this study, the relationship between a patient's psychosocial characteristics (self-reported in postal surveys in 2003) and the number of antibiotics they were prescribed (recorded in Finnish national registry data between 2004-2006) were analyzed for 19,300 working-aged Finns. Psychosocial characteristics included life satisfaction, a sense of coherence, perceived stress, hostility, and optimism. In a structural equation model, patients' adverse psychosocial characteristics were not related to increased antibiotic prescriptions in the subsequent three years. However, these characteristics were strongly associated with poor general health status, which in turn was associated with an increased number of subsequent antibiotic prescriptions. Furthermore, mediation analysis showed that individuals who used healthcare services more frequently also received more antibiotic prescriptions. The current study does not support the view that patients' adverse psychosocial characteristics are related to an increased number of antibiotic prescriptions. This could encourage physicians to actively discuss treatment options with their patients.